Analisis Faktor-Faktor yang Mempengaruhi Ketimpangan Pembangunan di Provinsi Kalimantan Selatan - Cinthya, Nadya (PPJP ULM, 2018)
This research is conducted to (1) find out whether the content of naturalresources, demographic condition, mobility of goods and services, the concentrationof economic activity, and development fund allocation together significantly influencethe development inequality in South Kalimantan Province; (2) to know the mostdominant factor influencing development disparity in South Kalimantan Province.The technique of data analysis in this research is Williamson index analysis and paneldata regression analysis with the Fixed Effect model. The result of panel data regression states that natural resource content,demographic condition, mobility of goods and services, the concentration of economicactivity, and development fund allocation have a significant effect on developmentdisparity in South Kalimantan Province. The demographic condition factor is themost dominant factor affecting development disparity in South Kalimantan Provincein 2012-2016.